The management of pediatric obesity and diabetes - Ferry, Robert J. (Robert Jean) Jr (Nutrition and health., 2011)
The twin epidemics of obesity and type 2 diabetes mellitus (T2DM) continue to affect an ever increasing number of children, adolescents, and young adults. Management of Pediatric Obesity and Diabetes provides healthcare trainees and professionals with practical, comprehensive, and contemporary approaches to the pediatric patient at risk for obesity, T2DM, and related conditions. A unique guide on the subject, this volume provides clinical paradigms for diagnosis and management of pediatric T2DM and related conditions, while succinctly describing state-of-the-art basic and clinical sciences underlying these problems. The chapters in this volume are independent and concise. Each chapter focuses on a key clinical issue or mechanism of disease. Providing practical, data-driven resources based upon the totality of the evidence, this important text helps the reader understand the basics of pediatric obesity and T2DM and implement strategies to prevent and treat obesity and diabetes in children and adolescents. Management of Pediatric Obesity and Diabetes provides health professionals across many areas of research and practice with up-to-date, well-referenced, and comprehensive evidence on identification, treatment, and prevention of these chronic, serious, metabolic diseases in children. This volume will serve the reader as the most authoritative resource in the field to date.